The Effectiveness of Urban Forest in Absorbing CO2 Emission at Rajekwesi Type A Terminal - Oktavianus Cahya Anggara; Laily Agustina Rahmawati (Jurnal Ilmu Lingkungan, 2021)
The terminal in Bojonegoro District is Rajekwesi Type A Terminal. It is located close to the CBD that has resulted in a decrease in environmental quality, due to gas emissions released by motor vehicles. The decrease in environmental quality can be overcome with an ecological approach, for example by creating or expanding green open spaces (urban forest). This study aimed to provide information about the capability of urban forest of the terminal to absorb CO2 emissions. This study began with a survey counting the number of motor vehicles at the gateway of the terminal on Sunday, Monday, Wednesday, Friday and Saturday for 24 hours. Then, the measurement of tree biomass was carried out using the nondestructive method. After the data was collected, the amount of CO2 emissions from motor vehicles was calculated by adding up CO2 emissionsin a stationary (idle) position when it was moving. The total CO2 emissions of motor vehicles at Rajekwesi Type A Terminal was 292.058,087 kgCO2/year. The amount of carbon sink (Wtc) of a tree was calculated by multiplying the total biomass (Wt) by the carbon concentration. The amount of Wtc at the urban forest of Rajekwesi Type A Terminal was 4.366,059 kg/year. After the amount of Wtc was found out, the amount of CO2 absorbed by the tree could be found out by multiplying Wtc by the conversion constant of the carbon (C) element to CO2 (3,67). The amount of CO2 absorbed by the trees at the urban forest of Rajekwesi Type A Terminal was 16.023,44 kgCO2/year. If they were compared, the absorption of CO2 was still much smaller than the emission rate. Thus, the function of the urban forest of terminal as an absorber of CO2 emissions was still not optimal.